Photovoltaic modules and sealant compositions having improved resistance to potential induced degradation
By using copolymers of copolymers of copolymers of copolymers of copolymers of ethylene and vinyl acetate and enhanced anti-PID copolymers in the sealant of the photovoltaic module, the problem of photovoltaic modules being susceptible to potential-induced attenuation is solved, and the efficiency and service life of the module are significantly improved.
Patent Information
- Application Number
- CN201980013424.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2018-03-08
- Filing Date
- 2019-03-05
- Publication Date
- 2025-02-14
- Estimated Expiration
- 2039-03-05
AI Technical Summary
Photovoltaic modules are susceptible to potential-induced attenuation (PID) during use, resulting in reduced efficiency of solar cells or stopping power generation.
The resistance of the photovoltaic module to PID is enhanced by using a sealant composition comprising a copolymer of copolymer of copolymerized ethylene and vinyl acetate and an enhanced anti-PID copolymer.
It effectively reduces the possibility that the photovoltaic module is affected by PID and improves the efficiency and service life of the module.
Smart Images

Figure GDA0005134726690000202 
Figure GDA0005134726690000221 
Figure GDA0005134726690000231
Abstract
Description
Technical Field
[0001] Provided herein is a sealant composition for a photovoltaic module. The sealant composition comprises a copolymer of copolymerized ethylene and vinyl acetate and an enhanced anti-PID copolymer, wherein the enhanced anti-PID copolymer has the following general structure: E / X, wherein E is ethylene and X is a half ester of maleic anhydride; or E / X / Y, wherein E is ethylene, X is a half ester of maleic anhydride and Y is an alkyl acrylate. Also provided herein is a photovoltaic module comprising the sealant composition. The photovoltaic module is less susceptible to potential induced degradation than a photovoltaic module using a sealant that is primarily a copolymer of ethylene and vinyl acetate. Background Art
[0002] Several patents and publications are cited in this specification in order to more fully describe the state of the art to which the present invention relates. The entire disclosure of each of these patents and publications is incorporated herein by reference.
[0003] Photovoltaic modules are an important source of renewable energy. Specifically, they include solar cells that release electrons when exposed to sunlight. These solar cells, which are usually semiconductor materials that can be fragile, are usually encapsulated or sealed in a polymer material that protects them from physical impact and scratches. The encapsulated solar cells are generally also protected by glass or by another outer layer that resists weathering, abrasion or other physical damage.
[0004] Ideally, the sealant, glass layers, and other components in a photovoltaic module would protect the solar cells and not reduce the efficiency of converting light into electricity. However, the phenomenon of potential induced degradation ("PID") is a known problem that causes the solar cells to reduce or stop generating electricity when a photovoltaic module operates with large potentials between its solar cells and another part of the module (such as the frame). Therefore, one approach to addressing the PID problem is to design modules in which the solar cells are electrically isolated from the frame and other parts of the module, thereby preventing the generation of these large internal potentials or "polarizations." See, for example, U.S. Patent Application Publication No. 20120266943 to Li. In another approach, U.S. Patent No. 7,554,031 to Swanson et al. describes providing conductive paths between various parts of a photovoltaic module to minimize or prevent harmful polarizations.
[0005] It is believed that a number of different factors contribute to PID. For example, U.S. Patent Application Publication No. 2011 / 0048505 to Bunea et al. claims that PID can be reduced or eliminated by operating a solar cell under exposure to an increased percentage of solar UV radiation. However, without wishing to be bound by theory, migration of water and ions to the surface of the solar cell appears to be the primary mechanism of PID. Other factors that affect PID, such as the voltage at which the photovoltaic module is operated and the design of the circuitry, are believed to be secondary because they can affect the magnitude or direction of water and ion migration.
[0006] Specifically, it is assumed that diffused water and ions cause adverse electrochemical reactions that deactivate the pn junction of the solar cell. In this regard, in International Patent Application Publication No. WO2013 / 020128 to Aitken et al., it is claimed that PID can be reduced or eliminated by replacing the standard soda-lime glass in photovoltaic modules with a glass that is free of or substantially free of alkali ions, such as sodium ions. The importance of selecting a chemically appropriate antireflective coating has been discussed, for example, in S. Pingel et al., Potential Induced Degradation of Solar Cells and Panels, 35th IEEE Photovoltaic Specialists Conference (PVSC), Honolulu, 2010, 2817-2822. The rate of PID can be controlled by varying the Si to N ratio as a function of the refractive index, and therefore corresponding optical properties. In addition, U.S. Patent No. 8,188,363 to Xavier et al. claims that PID can be eliminated by inserting an electrically insulating fluorocarbon layer between the glass and the solar cell. The fluorocarbon layer may also act as a barrier to water or ion migration.
[0007] Furthermore, other important properties of photovoltaic modules are known to be adversely affected by high temperature and moisture content. These properties include, for example, mechanical integrity, electrical characteristics (such as volume resistivity, current leakage rate, and overall cell efficiency).
[0008] Therefore, it is important to understand and control the factors that affect the rate and magnitude of moisture ingress and ion migration in sealants. A sealant that effectively prevents or reduces the movement of water and ions within a photovoltaic module will allow greater flexibility in the design and operating conditions of the module. In addition, such a sealant will increase the efficiency and service life of the module by reducing or preventing PID.
[0009] From the foregoing it is apparent that a need exists for polymeric materials that, when used as encapsulants in photovoltaic modules, prevent or reduce potential induced degradation of solar cells. Summary of the invention
[0010] Therefore, in the first embodiment provided herein is a sealant composition for a photovoltaic module. The sealant composition includes a copolymerized ethylene-vinyl acetate copolymer (EVA) and a reinforced anti-PID copolymer A. The reinforced anti-PID copolymer A is E / X, wherein E is ethylene and X is a half ester of maleic anhydride, or E / X / Y, wherein E is ethylene, X is a half ester of maleic anhydride and Y is an alkyl acrylate.
[0011] The present invention also provides a photovoltaic module including the sealant composition, which is less susceptible to potential induced degradation than a photovoltaic module using a sealant mainly composed of a copolymer of ethylene and vinyl acetate.
[0012] In another embodiment, the present invention relates to a method for reducing potential induced degradation of a photovoltaic module, comprising the steps of providing a solar cell assembly, a glass layer and a sealant layer. The sealant layer having a sealant composition comprises a copolymer of copolymerized ethylene and vinyl acetate and an enhanced anti-PID copolymer. The enhanced anti-PID copolymer A is E / X, wherein E is ethylene and X is a half ester of maleic anhydride, or E / X / Y, wherein E is ethylene, X is a half ester of maleic anhydride and Y is an alkyl acrylate. A photovoltaic module having a structure of a glass layer / sealant layer / solar cell / sealant layer / back sheet assembly is manufactured and operated. Thereafter, the current generated by the photovoltaic module is observed over time. DETAILED DESCRIPTION
[0013] The following definitions are used herein to further define and describe the present disclosure. Unless otherwise limited in specific instances, these definitions apply to the terms as used throughout this specification.
[0014] Unless defined otherwise, all technical and scientific terms used herein have the same meaning as commonly understood by one of ordinary skill in the art to which the invention belongs. In the event of a conflict, the present specification, including the definitions set forth herein, will control.
[0015] All percentages, parts, ratios and the like used herein are defined by weight unless expressly stated otherwise in the context of a definition.
[0016] When the term "known to those skilled in the art", "conventional" or synonymous words or phrases are used herein to describe materials, methods or machinery, the term means that the materials, methods and machinery that are conventional at the time of filing this application are encompassed by the present embodiments. Also encompassed are materials, methods and machinery that are not currently conventional, but which have been recognized in the art as suitable for similar purposes.
[0017] As used herein, the terms "comprises / comprising," "includes / including," "contains," "characterized by," "has / having," or any other variation thereof, are intended to cover a non-exclusive inclusion. For example, a process, method, article, or apparatus that comprises a list of elements is not necessarily limited to only those elements but may include other elements not expressly listed or inherent to such process, method, article, or apparatus.
[0018] The transitional phrase "consisting of" excludes any element, step, or ingredient not specified in the claim, thereby closing the claim to include materials other than the impurities normally associated therewith. When the phrase "consisting of" appears in a clause in the body of the claim, rather than immediately following the preamble, it limits only the elements set forth in that clause; other elements are not excluded from the claim as a whole.
[0019] The transitional phrase "consisting essentially of limits the scope of a claim to the specified materials or steps and to those materials or steps that do not materially affect the basic and novel characteristic(s) of the claimed invention. 'Consisting essentially of' claims occupy a middle ground between closed claims written in 'consisting of' format and fully open claims drafted in 'comprising' format. Optional additives (in amounts appropriate for such additives) and minor impurities as defined herein are not excluded from the composition by the term "consisting essentially of.
[0020] When an open-ended term such as "comprising" is used herein to describe a composition, process, structure, or a portion of a composition, process, or structure, unless otherwise stated, the embodiments also include embodiments where the composition, process, structure, or a portion of a composition, process, or structure "consists essentially of" or "consists of."
[0021] In addition, in this regard, for clarity, certain features of the present invention described herein in the context of separate embodiments may also be provided in combination in a single embodiment. Conversely, for brevity, various features of the present invention described in the context of a single embodiment may also be provided individually or in any sub-combination.
[0022] The articles "a" and "an" may be used in conjunction with various elements and components of the compositions, processes or structures described herein. This is merely for convenience and to give a general sense of the composition, process or structure. Such descriptions include "one or at least one" of the elements or components. In addition, as used herein, singular articles also include descriptions of multiple elements or components unless it is obvious from the particular context that the plural is excluded.
[0023] In addition, unless expressly stated to the contrary, the conjunction "or" refers to an inclusive or, not an exclusive or. For example, the condition "A or B" is satisfied by any of the following: A is true (or present) and B is false (or absent); A is false (or absent) and B is true (or present); and both A and B are true (or present). For example, an exclusive "or" is indicated herein by terms such as "either A or B" and "one of A or B."
[0024] The term "about" means that amounts, sizes, formulations, parameters, and other quantities and characteristics are not and need not be exact, but may be approximate and / or larger or smaller as desired, reflecting tolerances, conversion factors, rounding, measurement errors, etc., and other factors known to those skilled in the art. In general, amounts, sizes, formulations, parameters, or other quantities or characteristics are "about" or "approximately", whether or not explicitly stated as "about" or "approximately".
[0025] In addition, unless otherwise explicitly stated, the scope set forth herein includes its endpoints. In addition, when amount, concentration or other values or parameters are given as ranges, one or more preferred ranges or a series of upper preferred values and lower preferred values, it should be understood that all ranges formed by any paired upper range or preferred value and any lower range or preferred value are specifically disclosed, regardless of whether such paired values are disclosed individually. The scope of the present invention is not limited to the specific values narrated when defining the scope.
[0026] The term "alkyl", such as "alkyl" or "alkoxy", as used herein, alone or in combination, refers to a saturated hydrocarbon group having 1 to 8 carbon atoms (with one substituent) and which may be branched or unbranched.
[0027] As used herein, the term "copolymer" refers to a polymer comprising copolymerized units resulting from the copolymerization of two or more comonomers. In this regard, copolymers may be described herein with reference to the constituent comonomers of the copolymer or the amounts of their constituent comonomers, such as "a copolymer comprising ethylene and 18% by weight of vinyl acetate" or similar descriptions. Such descriptions may be considered informal because they do not refer to the comonomers as comonomers; because they do not include conventional nomenclature for copolymers, such as the International Union of Pure and Applied Chemistry (IUPAC) nomenclature; because they do not use product-by-process characterized by a method; or for another reason. However, as used herein, a copolymer description with reference to the constituent comonomers of the copolymer or the amounts of their constituent comonomers means that the copolymer contains comonomers of the specified comonomer (a specified amount when specified). It follows that a copolymer is not the product of a reaction mixture containing a given amount of a given comonomer, unless explicitly stated as such in limited circumstances. The term "copolymer" may refer to a polymer consisting mainly of copolymerized units of two different monomers (a binary copolymer) or mainly consisting of two or more different monomers (a terpolymer consisting mainly of three different comonomers, a tetrapolymer consisting mainly of four different comonomers, etc.).
[0028] The term "laminate" (such as "laminated" or "laminated") as used herein, alone or in combination, refers, for example, to a structure having at least two layers that may be securely adhered or bonded to each other, optionally using heat and / or vacuum and / or positive pressure. The layers may be adhered to each other directly or indirectly. In this context, the term "directly" means that there is no additional material, such as an interlayer, sealant layer, or adhesive layer, between the two layers, and the term "indirectly" means that there is additional material between the two layers.
[0029] In a first embodiment, the present invention relates to a sealant composition for a photovoltaic module. The sealant composition includes a copolymer of ethylene and vinyl acetate and an enhanced anti-PID copolymer A, wherein the enhanced anti-PID copolymer is E / X, wherein E is ethylene and X is a half ester of maleic anhydride, or E / X / Y, wherein E is ethylene, X is a half ester of maleic anhydride and Y is an alkyl acrylate. A photovoltaic module comprising the sealant composition is also provided herein. The photovoltaic module is less susceptible to potential induced degradation than a photovoltaic module using a sealant that is primarily a copolymer of ethylene and vinyl acetate.
[0030] Photovoltaic module comprising a layer of a sealant composition as described herein, the layer of the sealant composition comprising a PID-resistant enhanced copolymer A that is resistant to potential induced degradation (PID). Without wishing to be bound by theory, it is believed that the sealant composition has a low permeability to ions, such as alkali metal cations, and in particular sodium cations. Thus, ions are prevented from reaching the surface of the solar cell, wherein the ions can cause the occurrence of PID.
[0031] The PID-resistant reinforced copolymer A is in the range of 1 wt.%-30 wt.% of the total weight of EVA and copolymer A, preferably in the range of 2 wt.%-20 wt.%, and most preferably in the range of 4 wt.%-15 wt.%.
[0032] The EVA of the sealant composition is copolymerized ethylene and vinyl acetate, wherein the vinyl acetate is in the range of 15 wt% to about 35 wt%, most preferably 25 wt.%-32 wt.%, based on the weight of the polymer, wherein the melt flow rate is 0.5 g / 10 min to 100 g / 10 min as measured at 190°C and 2.16 kg according to ASTM D1238.
[0033] The anti-PID copolymer A acting as a modifier for enhancing the anti-PID performance is an E / X copolymer, wherein X is a half ester of maleic anhydride. The E / X copolymer includes monomethyl maleate, monoethyl maleate (MAME), monopropyl maleate, monobutyl maleate or a combination thereof in the range of 12 wt.% to 25 wt.%, most preferably 15 wt.%-20 wt.% based on the weight of the polymer.
[0034] In a variation of the current embodiment, copolymer A is an E / X / Y copolymer, wherein X is monomethyl maleate, monoethyl maleate (MAME), monopropyl maleate, monobutyl maleate, or a combination thereof, in the range of 6 wt.% to 20 wt.%, most preferably 8 wt.%-15 wt.%, based on the weight of the polymer; wherein Y is methyl acrylate, ethyl acrylate, n-butyl acrylate, or isobutyl acrylate, in the range of 1 wt.% to 30 wt.%, most preferably 5 wt.%-15 wt.%, based on the weight of the polymer.
[0035] According to the method of the International Electrotechnical Commission: IEC TS 62804-1 technical specification, the photovoltaic module including the sealant composition of this embodiment passes 1000-1500 voltage under such conditions.
[0036] Suitable anti-PID copolymers A should have physical properties suitable for use in sealant compositions. Specifically, the sealant composition ideally has appropriate toughness and elasticity to cushion the solar cells and other electronic components of the photovoltaic module from physical impact. Also ideally, the sealant composition can be easily processed, for example, can be formed into thin sheets and can be laminated under standard conditions. Also ideally, the sealant composition has suitable optical properties, such as transparency to solar radiation when used on the light incident side of the photovoltaic module.
[0037] The sealant composition may add another polymer B different from EVA and copolymer A in the range of 0wt.%-20wt.% of the combination of EVA and copolymer A or more, provided that polymer B does not hinder the anti-PID performance and does not reduce the PV performance. Polymer B may be a polyolefin or ethylene copolymer other than the EVA and copolymer A employed in the sealant composition. Those skilled in the art will recognize that the addition of these additional polymers is within the scope of the present invention.
[0038] The sealant composition may also contain additives for achieving and controlling crosslinking, such as organic peroxides, inhibitors, and initiators. Suitable examples of crosslinking additives and the amounts of these additives are described in detail in U.S. Pat. No. 6,093,757 to F.-J. Pern, U.S. Pat. Publication No. 2012 / 0168982 to J. W. Cho et al., and 2012 / 0301991 to S. Devise et al., and in Advanced EVA-Based Encapsulants-Final Report January 1993-June 1997 by Holley, WW and Agro, SC, NREL / SR-520-25296, September 1998, Appendix D.
[0039] In addition, four particularly useful additives for use in sealant compositions are heat stabilizers, UV absorbers, hindered amine light stabilizers (HALS) and silane coupling agents. Suitable examples of the four additives and the amounts of these additives are described in detail in U.S. Pat. No. 8,399,096 to Hausmann et al.
[0040] The sealant composition may also include one or more other additives, suitable other additives may include but are not limited to plasticizers, processing aids, flow enhancing additives, lubricants, pigments, dyes, flame retardants, impact modifiers, nucleating agents, anti-caking agents (e.g., silica), dispersants, surfactants, chelating agents, coupling agents, adhesives, primers, reinforcing additives (e.g., glass fibers), other fillers, etc. Suitable other additives, additive levels, and methods of incorporating additives into copolymer compositions can be found in the 5th edition of the Kirk-Othmer Encyclopedia of Chemical Technology, published by John Wiley & Sons (New Jersey, 2004). Generally, the total amount of these other additives (if present) is less than 5 wt%, less than 3 wt%, less than 2 wt%, or less than 1 wt%, based on the total weight of the sealant composition.
[0041] The sealant composition can be made by any suitable process, such as melt mixing in an extruder with high shear melt mixing is preferred. Suitable high shear mixing equipment includes static mixers, rubber grinders, Brabender mixers, Buss kneaders, single screw extruders, twin screw extruders, heated or unheated twin roll mills, etc. Additional examples of suitable compounding processes and conditions can also be found in the Kirk-Othmer Encyclopedia and McGraw-Hill's Modern Plastics Encyclopedia (New York, 1995).
[0042] The sealant composition can be formed into a film or sheet by any suitable process. Information about these processes can be found in reference texts, such as the Kirk Osmo Encyclopedia, the Modern Plastics Encyclopedia, or the Wiley Encyclopedia of Packaging Technology, 2nd edition (Hoboken, 1997) compiled by A L Brody and K S Marsh published by Wiley-Interscience. For example, a sheet can be formed by dip coating, solution casting, compression molding, injection molding, lamination, melt extrusion, blown film, extrusion coating, tandem extrusion coating, or any other suitable procedure. Preferably, a sheet is formed by melt extrusion, melt coextrusion, melt extrusion coating, or tandem melt extrusion coating process.
[0043] In this regard, the terms "film" and "sheet" as used herein refer to a substantially planar continuous article. The term "continuous" as used in this context means that the length of the film or sheet is at least about 3 m, at least about 10 m, at least about 50 m, at least about 100 m, or at least about 250 m. In addition, the aspect ratio of the sheet, i.e., the ratio of length to width, is at least 5, at least 10, at least 25, at least 50, at least 75, or at least 100.
[0044] In addition, films differ from sheets in thickness; however, there is no industry standard for the exact thickness that distinguishes between films and sheets. However, as used herein, films are generally about 10 mils (0.254 mm) or less in thickness. Sheets are generally greater than about 10 mils (0.254 mm) in thickness. Unless otherwise limited in a particular example, the description herein also refers to films and sheets. However, for convenience, only one of these terms may be used in a given context.
[0045] In addition, the thin sheet comprising the sealant composition may have a smooth or rough surface on one or both sides. Preferably, the thin sheet has a rough surface on both sides to facilitate degassing during the lamination process. The rough surface can be produced by conventional processes (such as mechanical embossing). For example, the thin sheet after extrusion can be placed by a special surface of a mold roller close to the mold outlet. This mold roller imparts the required surface characteristics to one side of the molten polymer. Therefore, when the surface of such a textured roller has tiny peaks and valleys, the polymer thin sheet that can still be embossed cast on the textured roller will have a rough surface on the side in contact with the roller. The rough surface generally conforms to the valley and peak of the roller surface, respectively. Textured rollers are described in, for example, U.S. Patent No. 4,035,549 and U.S. Patent Application Publication No. 2003 / 0124296.
[0046] Photovoltaic modules comprising a layer of the sealant composition described herein are resistant to potential induced degradation (PID). Without wishing to be bound by theory, it is believed that the sealant composition has a low permeability to ions, such as alkali metal cations, and in particular sodium cations. Thus, the ions are prevented from reaching the surface of the solar cell, where they could cause damage to the solar cell.
[0047] Therefore, photovoltaic modules comprising sealant compositions are also provided herein. The structure of a photovoltaic module that may appropriately include a sealant composition includes, but is not limited to, the structure described in detail in U.S. Patent No. 8,399,081 to Hayes et al. The layer of the sealant composition may be replaced by any polymer layer described by Hayes et al. Preferably, the layer of the sealant composition described herein may be replaced by any sealant layer described by Hayes et al., including a front or sun-facing sealant layer and a back or non-sun-facing sealant layer. More preferably, the layer of the sealant composition described herein is replaced by a sealant layer disposed between a solar cell and a sodium ion-containing glass sheet. Even more preferably, the layer of the sealant composition described herein is replaced by a sealant layer disposed between a solar cell and a sodium ion-containing glass sheet on the front or sun-facing side of the photovoltaic module.
[0048] Moreover, the layers of the sealant compositions described herein are used in combination with any sealant layer described by Hayes et al. More specifically, a preferred photovoltaic module has a structural glass / first sealant layer / solar cell assembly / second sealant layer / flexible backsheet or glass, wherein one of the first or second sealant layers comprises EVA and E / X copolymer A described herein, and the other of the first and second sealant layers can be any sealant layer described by Hayes et al. In this preferred photovoltaic module, the first and second sealant layers can be front or back sealant layers. In addition, when the sealant layer so disposed is replaced by the first and second sealant layers, any photovoltaic module comprising a sealant layer disposed between the solar cell assembly and the sodium ion-containing glass sheet is a preferred photovoltaic module, wherein one of the first or second sealant layers comprises EVA and E / X copolymer A described herein, and the other of the first or second sealant layers can be any sealant layer described by Hayes et al.
[0049] Photovoltaic modules also include solar cell assemblies. These assemblies include one or more solar cells. The two most common types of photovoltaic modules include wafer-based solar cells or thin-film solar cells. Photovoltaic modules including wafer-based solar cells generally have a structure including the following layers: glass / sealant / (one or more) solar cells / sealant / glass, or glass / sealant / (one or more) solar cells / sealant / flexible backsheet.
[0050] Thin-film solar cells are an alternative to wafer-based solar cells. Materials commonly used for such cells include amorphous silicon (a-Si), microcrystalline silicon (μc-Si), cadmium telluride (CdTe), copper indium selenide (CuInSe2 or CIS), copper indium / gallium diselenide (CuInSe2 or CIS), and copper indium / gallium diselenide (CuInSe2). x Ga (1-x)Se2 or CIGS), light absorbing dyes, organic semiconductors, etc. By way of example, thin film solar cells are described in, for example, U.S. Pat. Nos. 5,507,881, 5,512,107, 5,948,176, 5,994,163, 6,040,521, 6,123,824; 6,137,048, 6,288,325, 6,258,620, 6,613,603, and 6,784,301. and U.S. Patent Publication Nos. 20070298590, 20070281090, 20070240759, 20070232057, 20070238285, 20070227578, 20070209699, 20070079866, 20080223436, and 20080271675.
[0051] Thin film solar cell assemblies typically include a substrate. Multiple layers of light absorbing and semiconductor material layers are deposited on the substrate. The substrate can be glass or a flexible film. The substrate is also referred to as a superstrate in those modules where it faces the incident sunlight. Thin film solar cell assemblies may also include a conductive coating, such as a transparent conductive oxide (TCO) or wire, generally deposited on the semiconductor material. Similar to wafer-based solar cell assemblies, thin film solar cell assemblies may be sandwiched between polymer sealant layers or laminated between polymer sealant layers, and this structure may in turn be sandwiched between external protective layers or laminated between external protective layers.
[0052] The thin film solar cell assembly may have only one surface laminated to the polymer sealant layer, specifically, the surface opposite to the substrate or superstrate. In these solar cell modules, the sealant layer is most often in contact with and laminated to the external protective layer. For example, a thin film solar cell module may have a laminated structure that includes, in order of position from the front or sun-facing side to the back or non-sun-facing side, (1) a thin film solar cell assembly with a superstrate on the front sun-facing side, (2) a polymer back sealant layer, and (3) a back protective layer or "back sheet". In this structure, the superstrate performs the function of the front protective layer.
[0053] Alternatively, the thin film solar cell module may have a laminate structure comprising, in order of position from the front or sun-facing side to the back or non-sun-facing side, (1) a front protective layer or "front sheet", (2) a polymer front sealant sheet, and (3) a thin film solar cell assembly having a substrate on its back or non-sun-facing side. In this structure, the substrate also performs the function of the back protective layer.
[0054] Suitable plastic film layers for the backsheet include, but are not limited to, the following polymers, such as polyesters (e.g., poly(ethylene terephthalate) and poly(ethylene naphthalate)), polycarbonates, polyolefins (e.g., polypropylene, polyethylene, and cyclic polyolefins), norbornene polymers, polystyrenes (e.g., syndiotactic polystyrenes), styrene-acrylate copolymers, acrylonitrile-styrene copolymers, polysulfones (e.g., polyethersulfone, polysulfone, etc.), nylons, poly(urethanes), acrylic polymers, cellulose acetates (e.g., cellulose acetate, cellulose triacetate, etc.), cellophane, poly(vinyl chloride) (e.g., poly(vinylidene chloride)), fluorinated polymers (e.g., polyvinyl fluoride, polyvinylidene fluoride, polytetrafluoroethylene, ethylene-tetrafluoroethylene copolymers, etc.), and combinations of two or more thereof. The plastic film may also be a biaxially oriented polyester film (preferably a poly(ethylene terephthalate) film) or a fluorinated polymer film (e.g., and Films available from EI duPont de Nemours and Company, Wilmington, DE (DuPont). In addition, the films used herein may be in the form of multilayer films, such as fluoropolymer / polyester / fluoropolymer multilayer films (e.g., available from Isovolta AG., Austria, or Madico, Woburn, MA). / PET / or TPT laminate films). These same materials are also suitable for use in flexible front sheets when transparent.
[0055] As used herein, the term "glass" includes window glass, plate glass, silicate glass, sheet glass, low iron glass, tempered glass, tempered low iron glass, tempered glass without CeO, float glass, tinted glass, specialty glass (such as those containing ingredients to control solar heating), coated glass (such as those sputtered with metal compounds (such as silver or indium tin oxide) for the purpose of controlling sunlight), low E glass, Toroglas TM Glass (Saint-Gobain NAInc., Trumbauersville, PA), Solexia TM Glass (PPG Industries, Pittsburgh, PA) and Starphire TMGlass (PPG Industries, Inc.) These and other specialty glasses are described, for example, in U.S. Pat. Nos. 4,615,989, 5,173,212, 5,264,286, 6,150,028, 6,340,646, 6,461,736, and 6,468,934.
[0056] Other materials (such as polymeric films) may be replaced by one or more of the glass layers in both types of photovoltaic modules. However, the photovoltaic modules of the present invention preferably include at least one glass layer. When the sealant composition described herein is used for the sealant layer, these photovoltaic modules provide significantly greater stability with respect to PID when compared to photovoltaic modules including conventional EVA sealants. In photovoltaic modules in which the photovoltaic module comprises glass, the improvement in stability is greater. Preferably, the glass is not a low sodium or low alkali glass, such as the glass described in International Patent Application Publication No. WO2013 / 020128.
[0057] When the photovoltaic module comprises more than one sealant layer, the additional (one or more) sealant layers may comprise a sealant composition as described herein. Alternatively, the additional (one or more) sealant layers may comprise other polymeric materials, such as acid copolymers, ionomers of acid copolymers, ethylene / vinyl acetate copolymers, poly(vinyl acetals) (including sonic grade poly(vinyl acetals)), polyurethanes, poly(vinyl chloride), polyethylenes (e.g., linear low density polyethylene), polyolefin block copolymer elastomers, copolymers of α-olefins and α,β-ethylenically unsaturated carboxylic acid esters) (e.g., ethylene methyl acrylate copolymers and ethylene butyl acrylate copolymers), silicone elastomers, epoxy resins, any sealant layer described by Hayes et al., and combinations of two or more of these materials.
[0058] The thickness of each sealant layer in the photovoltaic module can each be in the range of about 5 mils to about 40 mils (about 0.125 mm to about 1 mm), or about 2 mils to about 30 mils (about 0.250 mm to about 0.625 mm), or about 15 mils to about 20 mils (about 0.381 mm to about 0.505 mm). When the sealant layer is in the form of multiple layers, the total thickness of the multilayer sealant falls within the ranges set forth above. In addition, the photovoltaic modules described herein may have more than one sealant layer, such as a front sealant layer (in front of the solar cell) and a back sealant layer (behind the solar cell). Each of these sealant layers has a total thickness as set forth above.
[0059] Photovoltaic modules comprising the sealant composition can be made by any suitable process. Photovoltaic modules are most often made by vacuum lamination processes, such as those described in U.S. Patent No. 5,593,532. Alternatively, photovoltaic modules can be made by autoclave lamination processes, such as those described in U.S. Patent No. 7,763,360 and U.S. Patent Publication No. 2007 / 0228341 for glass laminates. However, non-autoclave lamination processes can also be used. Some examples of suitable non-autoclave lamination processes are also described in U.S. Patent Nos. 7,763,360 and 8,637,150.
[0060] It is believed that one of ordinary skill in the art will be able to make any adjustments that may be needed to the lamination process. For example, if the melt index of the sealant composition described herein is increased relative to the melt index of a conventional sealant layer, then reasonable adjustments to the process include lowering the lamination temperature or reducing the cycle time.
[0061] The following examples are provided to describe the present invention in more detail. These examples, which set forth specific embodiments and preferred modes presently contemplated for implementing the present invention, are intended to illustrate, not to limit, the present invention.
[0062] Examples
[0063] Materials and methods
[0064] Unless otherwise stated, the following materials were used throughout the Examples listed in Table 1, Table 2, and Table 3:
[0065] Annealed float glass—AGC Solite 145 mm x 155 mm x 3.2 mm, AGC Flat Glass North America, Alpharetta, GA
[0066] Backsheet—Dun-Solar 1200TPT, Dunmore Corp., Bristol, PA
[0067] ●Solar cell—Motech monocrystalline XS125-165R, Motech Industries, Inc., Tainan City, Taiwan, China
[0068] ●Wires, tabbing ribbon, busbars—Wuxi Sveck Technology, Wuxi, China
[0069] ○ Composition—62% tin, 36% lead, 2% silver
[0070] ○Interconnection ribbon—0.16mm×2mm
[0071] ○Busbar—0.2mm×5mm
[0072] ● Junction box—Renhe Solar, model PV-RH06-60, Renhe Solar, Zhejiang, China
[0073] ●Sealant (used as shown in Table 1 and Table 2)
[0074] o STR15420P, a commercially available EVA sealant from STR Holdings, Enfield, CT
[0075] ○HZ 406P, a commercially available EVA encapsulant from Hangzhou First Applied Materials, Hangzhou, China
[0076] ○ EN1 to EN4 containing EVA and E / MAME are as follows:
[0077] EVA—ethylene / vinyl acetate copolymer, containing 28 wt% copolymerized units of vinyl acetate, based on the total weight of the copolymer, and having a melt flow rate of 3.0 g / 10 min as measured at 190° C. and 2.16 kg according to ASTM D1238;
[0078] E / MAME - ethylene / ethyl maleate copolymer, comprising 15 wt% of copolymerized units of ethyl maleate, based on the total weight of the copolymer, and as described in accordance with ASTM D1238 at 190°C and
[0079] 400 g / 10 min., measured at 2.16 kg;
[0080] The specific formulations of sealants EN1-EN4 containing E / MAME are given in Table 1. The crosslinker was tert-butyl peroxycarbonate 2-ethylhexyl ester (TBEC) ( TBEC, Arkema). Crosslinking aid, triallyl isocyanurate (TAIC, Ciba). Light stabilizer is bis(2,2,6,6,-tetramethyl-4-piperidinyl) sebacate (Tinuvin 770, Ciba). Silane coupling agent is 3-methacryloxypropyltrimethoxysilane (KBM-503, Shin-Etsu Chemical). UV absorber is [2-hydroxy-4-(octyloxy)phenyl]phenyl ketone (Chimassorb 81, Ciba). All additives were used without further purification, and the additive formulations were based on 100 parts of the EVA and EMAME copolymer blend.
[0081] The cast sheets of EN1 to EN4 used as sealants in Tables 2 and 3 were prepared as follows. The EVA was soaked with silane coupling agent overnight for a minimum of eight hours. A concentrate containing the remaining additives (i.e., crosslinking agent, crosslinking aid, light stabilizer, and UV absorber) was prepared with the EVA resin to improve the uniformity of the final formulated compound. The silane-soaked EVA, concentrate, and EMAME resin were uniformly mixed and fed into the hopper of a twin-screw extruder with a set temperature of less than 110°C to prevent premature crosslinking of the resin matrix.
[0082] Table 1. EVA and EMAME sealant formulations
[0083]
[0084] The photovoltaic modules of Tables 2 and 3 were formed by lamination according to the following method. Annealed float glass (AGC Solite 145 mm×155 mm×3.2 mm, AGC Flat Glass North America, Alpharetta, Georgia) was rinsed with deionized water and dried. The following module configuration was obtained: glass / front sealant / one solar cell / back sealant / back sheet. The front sealant and back sealant used are described in the examples of Tables 2 and 3. The solar cell (XS125-165R, Motech Industries, Tainan, Taiwan) was monocrystalline and connected with a 0.16 mm×2 mm ribbon (Wuxi Swick Technology, Wuxi, China). A 0.2 mm×5 mm busbar (Wuxi Swick Technology, Wuxi, China) was electrically isolated from a Dunsolar 1200TPT back sheet (Dunsolar, Bristol, Pennsylvania).
[0085] The vacuum lamination cycle was set at 150°C with a treatment time of 18 minutes, 4 minutes of vacuum time and 13 minutes of pressurization time at a constant pressure of 1000 mbar. The vacuum laminator was a Meier Icolam 2515 model (NPC-Meier GMBH, Bocholt, Germany). The micromodule was removed from the vacuum laminator and allowed to cool to ambient temperature. The busbars were welded to the junction box, which was attached to the module with a sealant.
[0086] The PID of photovoltaic modules was tested according to the following method. The modules were glued to all four edges of the glass cover sheet with 3M 1-inch aluminum-based tape (3M Company, Saint Paul, MN). The front surface of the module was completely covered with untreated aluminum foil. The modules with aluminum foil were kept in an environmental chamber (Model SE-3000-4, Thermotron Industries, Holland, MI) at 60°C and 85% relative humidity for 96 hours, while a voltage potential of -1 kV was applied between the aluminum foil and the solar cell for 96 hours according to technical specification IEC TS 62804-1.
[0087] After the 96-hour test period, the modules were monitored by power measurement. The power output of the modules was measured according to the IEC 16215 method using a Spire SPI-SUN Simulator 4600SLP (Spire Group LLC, Ridgefield, CT) with an AMI 1.5 light source.
[0088] The solar modules made with commercially available EVA-based sealants in Comparative Examples CE1 and CE2 lost 90% and 78% of their module power, respectively. Thus, a potential of one kilovolt or 1000V would significantly reduce the power, causing PID on both modules in CE1 and CE2. The solar modules made with sealants comprising EMAME and EVA copolymers in Example EX1 (sealant containing 5 wt% of EMAME), Example EX2 (sealant containing 10 wt% of EMAME), Example EX3 (sealant containing 15 wt% of EMAME), and Example EX4 (sealant containing 20 wt% of EMAME) all lost less than 5% of their initial power or retained more than 95% of their initial power. Thus, the presence of EMAME (even at 5 wt.% in Example EX1) significantly improved power retention and significantly reduced the impact of PID.
[0089] Table 2. PID conditions: 60°C / 85% RH / -1000V (with aluminum foil)
[0090]
[0091] Table 3 lists another group of photovoltaic modules and summarizes the power maintained after the modules were exposed to -1500V and 85°C / 85% relative humidity (RH). These modules are mounted with aluminum frames and no aluminum foil is used at this higher voltage potential. Therefore, the glass of the module is exposed to 85% RH. Comparative Examples CE3 to CE4 have commercially available EVA sealants, STRSolar 15420P and Hangzhou First 406P, respectively. Examples EX5 to EX8 have EVA and E / MAME-based sealants, EN1 to EN4. The power retention results of the 1500V and 85°C / 85% RH tests at 48 hours and 96 hours show that the photovoltaic modules with sealants EN1 to EN4 containing 5% to 20% EMAME all exhibit a PID reduction of less than 5%, that is, greater than 95% of the power is maintained during the test period. In contrast, photovoltaic modules with conventional EVA encapsulants in Comparative Examples CE3 and CE4 lost 30% and 65% of the module's initial power, respectively, due to PID within 96 hours under the test conditions.
[0092] Table 3. PID conditions: 85°C / 85% RH / -1500V (without aluminum foil)
[0093]
[0094] Although certain preferred embodiments of the present invention have been described and specifically illustrated above, it is not intended that the present invention be limited to such embodiments. Various modifications may be made without departing from the scope and spirit of the present invention as set forth in the following claims.
Claims
1. A photovoltaic module comprising a sealant layer and a solar cell assembly, the sealant layer comprising a sealant composition comprising a blend of a copolymer of ethylene and vinyl acetate (EVA) and a reinforced copolymer A against potential induced degradation (PID), wherein the sealant composition provides a power output stability of >90% of the initial power output after exposure to damp heat and a voltage potential of 1500 V for up to 96 hours, - wherein the copolymer A is an E / X copolymer, wherein E is ethylene, X is a half ester of maleic anhydride, and is monomethyl maleate, monoethyl maleate MAME, monopropyl maleate, monobutyl maleate or a combination thereof, and X is in the range of 12 wt.% to 25 wt.% of the weight of the copolymer A; -or wherein copolymer A is an E / X / Y copolymer, wherein E is ethylene, X is a half ester of maleic anhydride and is monomethyl maleate, monoethyl maleate MAME, monopropyl maleate, monobutyl maleate or a combination thereof, X is in the range of 6 wt.% to 20 wt.% based on the weight of the copolymer A, wherein Y is methyl acrylate, ethyl acrylate, n-butyl acrylate or isobutyl acrylate or a mixture thereof, Y is in the range of 1 wt.% to 30 wt.% based on the weight of the copolymer A. 2 . The photovoltaic module according to claim 1 , wherein the copolymer A is in the range of 1 wt. % to 30 wt. % of the total weight of the EVA and the copolymer A. 3 .
3. The photovoltaic module of claim 1, wherein the sealant composition passes 1000 voltage potential under such conditions according to IEC TS 62804-1 technical specification.
4. The photovoltaic module of claim 1, wherein the copolymer of the sealant composition is copolymerized ethylene and vinyl acetate, wherein the vinyl acetate ranges from 15 wt% to about 35 wt% of the weight of the EVA.
5. The photovoltaic module of claim 1, wherein the copolymer A is the E / X copolymer, and X is present in an amount ranging from 15 wt.% to 20 wt.% of the weight of the copolymer A. The photovoltaic module of claim 1 , wherein copolymer A is the E / X / Y copolymer.
7. The photovoltaic module of claim 1, wherein copolymer A is the E / X / Y copolymer and X is present in an amount ranging from 8 wt.% to 15 wt.% of the weight of copolymer A; and wherein Y is present in an amount ranging from 5 wt.% to 15 wt.% of the weight of copolymer A.
8. The photovoltaic module of claim 1, further comprising one or more glass layers, one or more flexible backsheet layers, or a second encapsulant layer that may be the same as or different from the encapsulant layer.
9. The photovoltaic module of claim 1, wherein the sealant layer is in the form of multiple layers.
10. The photovoltaic module according to claim 1, wherein the copolymer A is in the range of 2 wt.% to 20 wt.% of the total weight of the EVA and the copolymer A.
11. The photovoltaic module according to claim 1, wherein the copolymer A is in the range of 4 wt.% to 15 wt.% of the total weight of the EVA and the copolymer A.
12. The photovoltaic module of claim 1, wherein the copolymer of the sealant composition is copolymerized ethylene and vinyl acetate, wherein vinyl acetate is in the range of 25 wt.% to 32 wt.% of the weight of the EVA.
Citation Information
Patent Citations
Glass laminates for threat resistant window systems
US20030124296A1
System and method for making an improved thin film solar cell interconnect
US20070079866A1
Thin film solar cell and its fabrication process
US20070209699A1
Method for patterning a photovoltaic device comprising CIGS material using an etch process
US20070227578A1
Solar control laminates
US20070228341A1